Ranolazine Induced Bradycardia, Renal Failure, and Hyperkalemia: A BRASH Syndrome Variant - Syed Arsalan Akhter Zaidi; Danial Shaikh; Muhammad Saad; Timothy J. Vittorio (Case Reports in Medicine)
Ranolazine is a well-known antianginal drug, that was first licensed for use in the United States in 2006. It was objectively shown to improve exercise capacity and to lengthen the time to symptom onset in patients with coronary artery disease. The most commonly reported side effects of ranolazine include dizziness, headache, constipation, and nausea. Here, we describe a case of bradycardia, hyperkalemia, and acute renal injury in the setting of ranolazine use. Our patient is an 88-year-old female who presented with abdominal pain, nausea, and vomiting. Her medical comorbidities included hypertension, diabetes, CAD, heart failure with preserved ejection fraction, paroxysmal atrial fibrillation, hypothyroidism, and a history of cerebrovascular accident without any residual deficits. Her prescription regimen included amlodipine, furosemide, isosorbide mononitrate, levothyroxine, metformin, omeprazole, and ranolazine. Physical examination was remarkable for bradycardia and decreased breath sounds in the left lower lung field. Laboratory studies were significant for a serum potassium level of 6.8 mEq/L and a serum creatinine level of 1.6 mg/dL. She was given insulin with dextrose, sodium polystyrene, and calcium gluconate in addition to fluids. Her bradycardia and renal function worsened over the next 24 hours. Ranolazine was discontinued. Metabolic derangements were treated appropriately. After 48 hours from presentation, potassium and renal function returned to baseline and her heart rate improved to a range of 60–100 bpm. She was discharged with an outpatient cardiology follow-up. Ranolazine treatment was not continued upon discharge. In summary, our case illustrates an association between ranolazine and renal failure induced hyperkalemia, leading to conduction delays in the myocardium. Though further studies are warranted, we suspect that this is a variant of the recently described BRASH syndrome. We propose that in cases such as ours, along with treatment of the hyperkalemia, medication review and removal of any offending agent should be considered.